ANALYSIS OF PHYSIOLOGICAL CHARACTERISTICS OF MIX DOUBLE BADMINTON ATHLETE DURING MATCH - IKHWAN HIDAYAT (NIM : 21715003), IWA
Background: Badminton is Indonesian pride in The Olympics. Nowadays, Indonesian mixed doubles are dominating in international competitions, but the achievement in this category is still inconsistent. To maintain good performance, appropriate training programs are required. Athlete’s physiological data are needed for customizing the athletes training program design. Therefore, Purpose of this study is to identify and analyze the physiological characteristics of Badminton mixed double athletes. The results of this study can be a preliminary data for coach to create a proper and effective training program. Method: The method used in this research is descriptive quantitative. This study was conducted in two phases. First phase is laboratory test, took place in FPOK UPI Lab and then the second phase is badminton simulation match, was held in PB Mutiara Cardinal Bandung gymnasium. The samples used in this study are mixed double players from a top national level badminton club, age ranging from 16-17 years old. Data measured in laboratory is VO2max Level, tested with COSMED CPET treadmill and data measured in match simulation are: Lactate Acid Level, measured using Acutrend and Heart Rate & Energy Expenditure, monitored with Polar RC3. Results: Mean value V02max of male athlete's 56.4 ± 5.7 (mL/kg/min) and female 45.2 ± 3.6 (mL/kg/min), There is a significant difference between male and female athletes with (p<0.05). Average heart rate of male athlete 139.8 ± 6.7 (bpm) and female 156.5 ± 8.1 (bpm) during match time, there is a significant difference between male and female athletes with (p<0.01), then the average lactic acid after the match is, the male 3.0 ± 0.8 (mmol/L) and female 4.5 ± 1.5 (mmol/L), and there is a significant difference between male and female athletes with (p<0.01), wheres there is no significant difference in energy expenditure with (p>0.05). Conclusion: The results show there are significant differences in the levels of V02max, average heart rate and lactic acid levels between male and female athletes during match time. The large difference in physical condition between male and female athletes are very influential on field performance. With this result, expected the coach are able to design the right training program for athletes, so it’s can minimize the distance of physical ability difference between male and female athletes, than the performance of female athlete able to support and balance male athlete performance.